Determinants of the Transition from Work into Retirement - Monika Riedel; Helmut Hofer (Johannes Kepler University Linz, NRN - The Austrian Center for Labor Economics and the Analysis of the Welfare State, 2013)
This NEUJOBS research report is concerned with determinants for planned retirement from work in European countries, using data from the 2006 ad hoc module of the European Labour Force Survey. The research uses multivariate analysis, taking into account factors that affect retirement planning including personal as well as workrelated characteristics, and some characteristics of national pension systems. In the context of the NEUJOBS project, the key conclusions of the report is that the interaction between planned retirement age and personal and work-related variables is not identical across Europe. Sex as well as country type need to be taken into consideration. Our results hint at EU states being in different phases of the transition from physically demanding to intellectually demanding work environments, which relates to earlier planned retirement where working is physically more demanding. This interpretation, however, is very tentative due to the crude identification of job characteristics via broad ISCO and NACE codes.
Keywords: 330